2008
DOI: 10.1523/jneurosci.3368-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dynamic Processing of Afferent Signals in Frog Tonic and Phasic Second-Order Vestibular Neurons

Abstract: The sensory-motor transformation of the large dynamic spectrum of head-motion-related signals occurs in separate vestibulo-ocular pathways. Synaptic responses of tonic and phasic second-order vestibular neurons were recorded in isolated frog brains after stimulation of individual labyrinthine nerve branches with trains of single electrical pulses. The timing of the single pulses was adapted from spike discharge patterns of frog semicircular canal nerve afferents during sinusoidal head rotation. Because each el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 57 publications
6
32
0
Order By: Relevance
“…Using a micromanipulator, injection electrodes were inserted vertically into the hindbrain through the ventricular surface, ϳ150 m lateral to the visible midline in r5, corresponding to the center of the abducens nucleus. Transmitter receptor antagonists were applied by pressure pulse injection (0.5 bar; 50 ms) of a volume of 20 -50 nl, corresponding to a spherical bolus with a diameter of ϳ300 -450 m. The rather superficial location of the abducens nucleus ϳ50 m below the ventricular surface and the likely leakage through the electrode track into the bath solution (Pfanzelt et al, 2008) reduced the amount of injected blockers. The volume nonetheless covered the entire abducens nucleus, which spans across ϳ200 m (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Using a micromanipulator, injection electrodes were inserted vertically into the hindbrain through the ventricular surface, ϳ150 m lateral to the visible midline in r5, corresponding to the center of the abducens nucleus. Transmitter receptor antagonists were applied by pressure pulse injection (0.5 bar; 50 ms) of a volume of 20 -50 nl, corresponding to a spherical bolus with a diameter of ϳ300 -450 m. The rather superficial location of the abducens nucleus ϳ50 m below the ventricular surface and the likely leakage through the electrode track into the bath solution (Pfanzelt et al, 2008) reduced the amount of injected blockers. The volume nonetheless covered the entire abducens nucleus, which spans across ϳ200 m (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In frog, these second-order vestibular neurons (2°VN) separate into two distinctly different functional subgroups (tonic-phasic neurons) based on differences in intrinsic membrane properties and discharge characteristics. Correlated with these cellular properties, tonic and phasic 2°VN exhibit pronounced differences in the dynamics of the synaptic activation following stimulation of individual labyrinthine nerve branches [1]. A detailed physio-pharmacological analysis indicated that the two types of 2°VN are differentially embedded in inhibitory circuits that reinforce the cellular properties of these neurons, respectively, thus indicating a co-adaptation of intrinsic membrane and emerging network properties in the two neuronal subtypes.…”
mentioning
confidence: 95%
“…Correlated with these cellular properties, tonic and phasic 2°VN exhibit pronounced differences in the dynamics of the synaptic activation following stimulation of individual labyrinthine nerve branches [1]. A detailed physio-pharmacological analysis indicated that the two types of 2°VN are differentially embedded in inhibitory circuits that reinforce the cellular properties of these neurons, respectively, thus indicating a co-adaptation of intrinsic membrane and emerging network properties in the two neuronal subtypes.In a recently published model [1], available quantitative physiological data on intrinsic and synaptic properties of identified frog 2°VN were used to create a model that combines network parameters with a preliminary subthreshold conductance-based cellular model. While this model helps elucidating the contributions of different ion channels to the synaptic subthreshold responses, it cannot explain the distinctly different firing behavior of tonic and phasic 2°VN during a synaptic activation by vestibular nerve afferents.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Most of these studies concerned the effect of frequency on the sensitivity and phase of responses of individual neurons and demonstrate a relatively flat relationship for frequencies between 0.1 and 2.0 Hz with an increasing phase lead relative to velocity as the frequency of rotation increases. Although studies of central vestibular neurons in vitro have addressed many aspects of response linearity (Bagnall et al 2008;du Lac and Lisberger 1995;Pfanzelt et al 2008), little systematic work has been done in vivo to understand how the magnitude of stimulation influences responses of central vestibular neurons. The linearity of the responses of central neurons over a range of rotational stimuli has not been directly addressed in normal, alert animals, although such responses have been reported in cats with unilateral vestibular lesions (Heskin-Sweezie et al 2007).…”
mentioning
confidence: 99%